THE ORGANIZATION OF JUDICIAL AUTHORITY AS MEANS OF ANTICORRUPTION POLICY - Alexander Vasilyevich Malko; Konstantin Aleksandrovich Strus (Современная наука и инновации, 2022)
The article considers the ways of optimization of the organization of the judicial authority, providing formation of judicial authority as means of anticorruption policy are considered